Identification and Characterization of Seven New Exon 11-Associated Splice Variants of the Rat Mu Opioid Receptor Gene, OPRM1. Issue 1 (21st January 2011) - Xu, Jin; Xu, Mingming; Rossi, Grace C; Pasternak, Gavril W; Pan, Ying-Xian
Background: The mouse mu opioid receptor (OPRM1) gene undergoes extensive alternative splicing at both the 3'- and 5'-ends of the gene. Previously, several C-terminal variants generated through 3' splicing have been identified in the rat OPRM1 gene. In both mice and humans 5' splicing generates a number of exon 11-containing variants. Studies in an exon 11 knockout mouse suggest the functional importance of these exon 11-associated variants in mediating the analgesic actions of a subset of mu opioids, including morphine-6β-glucuronide (M6G) and heroin, but not others such as morphine and methadone. We now have examined 5' splicing in the rat. Results: The current studies identified in the rat a homologous exon 11 and seven exon 11-associated variants, suggesting conservation of exon 11 and its associated variants among mouse, rat and human. RT-PCR revealed marked differences in the expression of these variants across several brain regions, implying region-specific mRNA processing of the exon 11-associated variants. Of the seven rat exon 11-associated variants, four encoded the identical protein as found in rMOR-1, two predicted 6 TM variants, and one, rMOR-1H2, generated a novel N-terminal variant in which a stretch of an additional 50 amino acids was present at the N-terminus of the previously established rMOR-1 sequence. When expressed in CHO cells, the presence of the additional 50 amino acids in rMOR-1H2 significantly altered agonist-induced G protein activation with little effect on opioid binding. Conclusion: The identification of the rat exon 11 and its associated variants further demonstrated conservation of 5′ splicing in OPRM1 genes among rodents and humans. The functional relevance of these exon 11 associated variants was suggested by the region-specific expression of their mRNAs and the influence of the N-terminal sequence on agonist-induced G protein coupling in the novel N-terminal variant, rMOR-1H2. The importance of the exon 11-associated variants in mice in M6G and heroin analgesia revealed in the exon 11 knockout mouse implies that these analogous rat variants may also play similar roles in rat. The complexity created by alternative splicing of the rat OPRM1 gene may provide important insights of understanding the diverse responses to the various mu opioids seen in rats.